ANALISA PERBEDAAN KINERJA KEUANGAN PEMERINTAH KOTA KEDIRI SEBELUM DAN SESUDAH PEMBERLAKUAN ANGGARAN BERBASIS KINERJA - Widyastuti Ayu Lestari (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2009)
Target of this research is to find empirical evidence of differentiation of monetary independence storey and fiscal decentralization Government of Kediri before and after application of budget base on performance. Method which used in this research is monetary ratio consisting of independence ratio. fiscal decentralization. efficiency ratio and effectiveness ratio, for knowing monetary independence storey of region, fiscal decentralization storey; effectiveness and efficiency of PAD which workable of government. From calculation of the monetary ratio different test by using F-Test to know the existence of difference before and after application of budget based on performance. Result of calculation showed monetary independence storey is existence of difference before and after application of budget base on performance, fiscal decentralization storey there isn’t differentiation before and after application of budget base on performance, effectiveness storey of PAD and efficiency storey of PAD experiencing of difference before and after application of budget base on performance